PENGARUH KEPRIBADIAN, KEPUASAN KERJA DAN PERSON ORGANIZATON FIT TERHADAP KINERJA GURU DENGAN MEDIASI KOMITMEN ORGANISASIONAL (STUDI PADA YAYASAN SMA KESATRIAN 67 SEMARANG) - KIRKis Retno Wulandari, 12.4202.0040; Abdul Rozak, H.Hasan (Jurnal Mahasiswa Pasca Sarjana, 2014)
This study aims to examine and analyze the influence of personality, job satisfaction, Person Organization fit and organizational commitment on the Foundation Kesatrian 67 Senior High School Â Semarang. This study was conducted by taking Kesatrian 67 senior high school Semarang ( Kesatrian 1 and Kesatrian 2 Semarang). The population of this study is all Kesatrian 67 senior high schoolâs teachers (100 respondents). In this sampling technique using census with all the criteria of teachers who have taught for at least 2 years in Kesatrian 67 Senior High School Â Semarang .Source of data used is primary data and secondary data. Instrument or measuring instrument in this study using a questionnaire. The data have been processed are presented in the form of frequency tables and using statistical analytical The results of the study are as follows: Personality has a positive and significant impact on organizational commitment, job satisfaction has a positive and significant impact on organizational commitment, Person organization fit has a positive and significant impact on organizational commitment, personality has a positive and significant impact on the performance of teachers, job satisfaction has a positive and significant impact on teacher performance, Person organization fit has a positive and significant impact on teacher performance and organizational commitment has a positive and significant impact on teacher performance. Keywords: Personality, Job Satisfaction, Organization Person fit, Organizational Commitment, Teacher Performance